(untitled) (Международный научный журнал «Инженер», 2026)
This article discusses the defects that arise in rails, which are one of the main components of railway infrastructure, and their current maintenance. All measures related to the maintenance of railways are primarily aimed at improving the interaction between the rolling stock and the track. Irregularities in the track cause vertical and horizontal dynamic forces, which in turn increase the impact transmitted from the vehicle to the track and lead to the accumulation of residual deformations. This necessitates regular correction of the track in both the longitudinal and transverse profiles.In this regard, studying the rails and their operating conditions is considered a highly relevant issue. Today, many innovations and opportunities are being introduced in the transport sector of our country. Therefore, conducting scientific research using modern methodologies and reliable scientific foundations is highly appropriate.This article presents the scientific basis for the maintenance methods of rail defects.